(untitled) (Biocenosis, 2012)
The Compañía Nacional de Fuerza y Luz, as part of its commitment to environmental development of the country, conducts educational work on the efficient use of energy. To fulfill this task, has produced two multimedia used as a learning strategy that provides knowledge on the subject and the formation of values, skills and attitudes that encourage teachers and students in preschool, I and II cycles, a culture that contributes to the conservation of this resource. These programs are: Rational Use of Energy and Energy Park.